Pengaruh Upah Investasi dan Pengeluaran Pemerintah Terhadap Penyerapan Tenaga Kerja Terdidik di Provinsi Sumatera Barat - wardatul jannah; urmatul uska akbar (Universitas Negeri Padang, 2025)
According to the Central Bureau of Statistics, educated workers are workers who gain expertise through formal education such as schools or universities with the highest education completed by senior high school. The difficulty of educated workers getting jobs with high requirements, this study aims to determine and analyze how the influence of wages, investment (PMA, PMDN, regional equity participation) and government spending on the absorption of educated labor. The data used is obtained from the West Sumatra Central Statistics Agency and the Ministry of Finance's djpk in 2018-2023 with 19 districts / cities using the panel data regression method processed through eviews12 the results of the analysis show that regional equity participation is the only independent variable that has a negative and significant effect, While the variable of PMDN wages and government spending is not significant on the absorption of educated labor in 2018-2023 policy recommendations for further research can be carried out research on other factors that affect the absorption of educated labor in West Sumatra. The author suggests that the government review the wage policy and job search requirements in West Sumatra, it is hoped that the government can also pay attention to the quality of human resources in order to compete, and it is hoped that future researchers will add other variables to better represent the state of employment in Indonesia.